2011
DOI: 10.1111/j.1365-2966.2010.18016.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters of 62 eclipsing binary stars using the All Sky Automated Survey-3 data − I

Abstract: We present a detailed light-curve analysis of publicly available V-band observations of 62 binary stars, mostly contact binaries, obtained by the All Sky Automated Survey (ASAS)-3 project between 2000 and 2009. Eclipsing binaries are important astronomical targets for determining the physical parameters of component stars from the geometry of their orbits. They provide an independent direct method of measuring the radii of stars. We improved the ASAS determined periods and ephemerides, and obtained the Fourier… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 63 publications
9
55
3
Order By: Relevance
“…We successfully explained the asymmetry in its light curves. The spectroscopic mass ratio is q=0.378, which is similar to the results obtained by Duerbeck & Rucinski (2007) and Deb & Singh (2011). The orbital inclination is 76°.05(±0.08), which is close to the results (72°.8∼75°.0) of McFarlane & Hilditch (1987) and 74°.0 by Deb & Singh (2011).…”
Section: Absolute Geometrical and Starspot Parameterssupporting
confidence: 78%
See 1 more Smart Citation
“…We successfully explained the asymmetry in its light curves. The spectroscopic mass ratio is q=0.378, which is similar to the results obtained by Duerbeck & Rucinski (2007) and Deb & Singh (2011). The orbital inclination is 76°.05(±0.08), which is close to the results (72°.8∼75°.0) of McFarlane & Hilditch (1987) and 74°.0 by Deb & Singh (2011).…”
Section: Absolute Geometrical and Starspot Parameterssupporting
confidence: 78%
“…In 2007, Duerbeck & Rucinski (2007) carried out a medium precision radial velocity observation and obtained a spectroscopic mass ratio as q=0.37 (±0.01) for the system. Deb & Singh (2011) analyzed a V-band light curve observation obtained by the All Sky Automated Survey (ASAS). They obtained the physical parameters of AD Phe.…”
Section: Introductionmentioning
confidence: 99%
“…Lifang Li et al (2004) have discussed a model for contact binaries with a low total mass, where binary star evolves into a system with smaller mass-ratio and deeper envelope and concluded that some of the A-subtype contact binaries observed with low total mass could be W-subtype binaries in their later evolutionary stages. In order to understand any such transition in the presently studied W UMa binary, we draw mass-ratio versus period for the binary systems in Figure 8, and also overplotted the parameters of ∼ 300 contact binaries detected in several previous studies including many low mass A-subtypes and W-subtypes W UMa binaries (Pribulla et al, 2003;Deb & Singh, 2011;Eker et al, 2013;Yildiz & Dogan, 2013). The position of the binary system CSS J004259.3 + 410629 in the plot indicates its possible transition from W-subtype to A-subtype while undergoing a decrease in mass-ratio via magnetic braking through angular momentum loss and it may continue to evolve into a single star through merger.…”
Section: Discussionmentioning
confidence: 99%
“…Deb & Singh (2011) recently analysed light curves of 62 binary stars, of which most of them were contact binaries, and found a good correlation between the period and infra-red (J − K) colour as following (J − K) = (0.11 ± 0.01)P −1.19±0.08…”
Section: Parameter Relationships and Characterizationmentioning
confidence: 99%
“…Although the heuristic scan (Prša & Zwitter 2005a) is a Monte Carlo (MC) parameter scan that uses minimization methods for many iterations, each time updating the input parameter values determined in the previous iteration (Maceroni et al 2009;Deb & Singh 2011), we additionallyused the MC analysis by creating many artificial data sets from the observations with the same noise as observations, and analyzing them as before. As expected, the random displacement of the original data (3000 data sets for each filter were created) follows a normal distribution with a zero mean and the standard deviation of the observations in each filter.…”
Section: Light Curve Modelingmentioning
confidence: 99%